Independent purinergic mechanisms of central and peripheral chemoreception in the rostral ventrolateral medulla - Moreira, Thiago S (J Physiol, 2015)
The rostral ventrolateral medulla oblongata (RVLM) contains two functionally distinct types of neurons that control and orchestrate cardiovascular and respiratory responses to hypoxia and hypercapnia. One group is composed of the central chemoreceptor neurons of the retrotrapezoid nucleus, which provides a CO(2)/H(+)-dependent drive to breathe and serves as an integration centre and a point of convergence of chemosensory information from other central and peripheral sites, including the carotid bodies. The second cluster of RVLM cells forms a population of neurons belonging to the C1 catecholaminergic group that controls sympathetic vasomotor tone in resting conditions and in conditions of hypoxia and hypercapnia. Recent evidence suggests that ATP-mediated purinergic signalling at the level of the RVLM co-ordinates cardiovascular and respiratory responses triggered by hypoxia and hypercapnia by activating retrotrapezoid nucleus and C1 neurons, respectively. The role of ATP-mediated signalling in the RVLM mechanisms of cardiovascular and respiratory activities is the main subject of this short review.